Analisis Fungsi Humas Pemerintah pada Program Kerjasama TPAS - Indri Fitri Yuningsih; Aditya Ali (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
In this study, researchers will discuss the Analysis of the Public Relations Function of the Serang City Government towards the Cilowong Village community in the Cilowong TPAS Cooperation Program. Researchers conducted this research on Public Relations Protocol Serang City Government. This research was conducted to determine the public relations function of the Serang City government in the Cilwong Village community related to the Cilowong TPAS cooperation program. By using a qualitative research method with a descriptive approach, this research uses data collection methods with literature studies, interviews and observations. The results of the discussion in this study are descriptive narratives that explain the public relations of the Serang City Government to the people of Cilowong Village in the Cilowong TPAS cooperation program. Keywords: Cilowong Community, Public Relations Function, Serang City Government Public Relations.